Characteristics of Dairy Farmers and Dairy Cattle Management Systems in Junrejo Village, Junrejo District, Batu City, East Java Province - Nur Ducha; Heni Natalia Aritonang; Rizka Muizzu Aprilia; Adi Tiya Warman; Siti Zubaidah; Achmad Muzakky Dityana (International Journal of Technology, Food and Agriculture, 2026)
In Indonesia, dairy cattle farming is often done in a traditional or conventional maintenance. This study aims to determine the farmer characteristics and maintenance systems of dairy in Junrejo Village, Junrejo District, Batu City, East Java, Indonesia. This study used a survey approach and was observational in nature. Twenty dairy farmers were chosen as respondens because they had dairy cows that were lactation period. The data collected included farmer characteristics, land ownership, and livestock management systems. The data were analyzed using descriptive analysis. The results showed that the average age of farmers was 52.95±10.51 years, most of the farmers were of productive age with 33.54±12.45 years of farming experience. Most of the farmers were of productive age. Most of them (95.00%) were livestock farmer group dairy cattle. Dairy cattle ownership consisted of 2.50±1.79 dairy cows, 0.20±0.70 dairy bull, 1.42±1.22 heifers, 1.20±1.11 female calves, and 0.60±0.60 males calve. In conclusion, this study showed that farmer charateristics were of productive age, had experience in livestock farming, participated in livestock groups, and raised livestock primarily. Livestock maintenance was carried out in communal and individual pens, pen cleaning, and livestock bathing were performed twice a day.